BUDAYA ORGANISASIONAL MEMODERASI KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine moderate the organizational culture of transformational leadership and organizational commitment on teacher performance Dabin I Mintaragen Eastern District of Tegal Tegal, research was conducted on teachers Dabin I Mintaragen Eastern District of Tegal Tegal as many as 109 people using the study population. The statistical techniques used by the validation test, reliability test, normality test, classical assumptions, and test the feasibility of the model. The research method with the entire population of teachers Dabin I Mintaragen Eastern District of Tegal Tegal, corrections research and sampling techniques based on the status of education, tenure, class, age, gender. Variables used freely, bound and moderation research instrument using a questionnaire with items as an indicator of variable transformational leadership, organizational commitment, organizational culture and performance. Likert scale studies are 5-point range. Based on the survey results revealed that transformational leadership significant and positive impact on teacher performance, organizational commitment positive and significant impact on teacher performance, organizational culture positive and significant impact on teacher performance, organizational culture strengthen the influence of transformational leadership on teacher performance and organizational culture does not moderate commitment organizational on teacher performance. Keywords: Transformational leadership, organizational commitment, organizational culture, and the performance of teachers.